Peningkatan Adaptibilitas Gembili (Dioscorea esculenta L.) pada Lahan Pesisir dengan Penambahan Pupuk Amonium Sulfat (ZA) dan Mulsa Organik - Herison, Catur; Turmudi, Edhi; Handayaningsih, Merakati; Dewi, Kurnia Herlina (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2015)
Increasing plant capability to adapt on coastal land is very important aspect in the development alternative carbohydrate source food. The objective of this research is to determine the effect of ZA fertilizer and organic mulch on lesser yam’s adaptability based on its growth and yield. The experiment was conducted with a randomized completely block design arranged in a split plot with 3 replications. As the Main Plot were organic mulch levels, and as the Sub Plot were ZA fertilizer doses. The results showed that there was no interaction effect between ZA fertilizer and organic mulch on either growth or yield of lesser yam. Application of ZA fertilizer up to 200 kg ha improve lesser yam’s adaptability based on their vegetative growth. Organic mulch of rice paddy straw up to the rate of 20 ton ha-1 did not increase growth and yield of lesser yam in coastal sandy land.